Going unnoticed for 40 years: about the presence of the exotic Suaeda paradoxa (Chenopodiaceae, Suaedoideae) in Argentina - Jocou, Adriel I.; Minué, Carlos R.; Brignone, Nicolás F.; Gandullo, Ricardo (Phytotaxa, 2020)
As a part of ecologic studies conducted in wetlands of Patagonia, Argentina, and in the frame of taxonomic studies within Chenopodiaceae for South America, we collected specimens of Suaeda that did not match the features to any of the species currently known to the Flora of Argentina. The aim of this contribution is to report for the first time the presence of Suaeda paradoxa in Argentina, by the means of the study of living plants and herbarium material, original descriptions, type material, and complementing with a distribution map, photos, a diagnostic key, and a comparative table to the herbaceous species of Suaeda in Argentina. Also, some comments regarding ecological and distributional features are discussed. This is the first record of S. paradoxa outside its native distribution range.